A MULTI-RESIDUE METHOD FOR QUANTITATION OF ORGANOCHLORINE, ORGANOPHOSPHORUS AND SYNTHETIC PYRETHROID PESTICIDES IN COTTON SEEDS (Biological Sciences - PJSIR, 2022)
Analytical procedures have been developed for extraction, cleanup, identification and quantification of multipleresidues of organochlorine, organophosphorus and synthetic pyrethroid pesticides in cotton seeds, collected fromcottongrowing areas of Punjab and Sindh provinces of Pakistan. These methods are efficient and reliable and allowed lipidremoval to a large extent.